Strategic effects of product innovation, service quality, and relationship quality on brand equity - Hanaysha, Jalal R. M. (Canadian Center of Science and Education, 2015)
In highly competitive markets, building brand equity has become one of the first priorities for many organizations as it brings several benefits and reputation for them.Past researches have acknowledged that consumers look for brands which provide them with differential values through innovative product and service features.However, despite the importance of product innovation in determining an organization’s success, very limited studies have intended to examine its effect on brand equity.In the present study, we aim to examine the effect of product innovation on brand equity in Ma